CSR Disclosure and Tax Avoidance: Evidence from Indonesia’s Infrastructure Sector - Nur Alim Bahri (Phinisi Applied Accounting Journal, 2026)
This study aims to examine the effect of Corporate Social Responsibility (CSR) and profitability on tax avoidance among infrastructure sector companies listed on the Indonesia Stock Exchange during the period 2021–2023. A quantitative approach was employed using secondary data obtained from annual reports and sustainability reports. The sample was selected through purposive sampling, resulting in 57 observations. Tax avoidance was measured using the Effective Tax Rate (ETR), CSR was measured using the Corporate Social Responsibility Index (CSRI), and profitability was measured using Return on Assets (ROA). Data were analyzed using multiple linear regression with IBM SPSS Statistics 25. The results indicate that Corporate Social Responsibility (CSR) does not have a significant effect on tax avoidance. Profitability also does not significantly affect tax avoidance. However, CSR and profitability simultaneously have a significant effect on tax avoidance. These findings suggest that although each variable individually does not significantly explain tax avoidance practices, their combined effect contributes to explaining variations in corporate tax avoidance behavior. The implications of this study highlight the importance of strengthening CSR implementation and profitability management as part of efforts to enhance corporate tax compliance. Furthermore, the findings may serve as a reference for regulators in formulating policies to monitor and reduce tax avoidance practices.